NPY in rat retina is present in neurons, in endothelial cells and also in microglial and Müller cells - Álvaro, Ana Rita (2007)
NPY is present in the retina of different species but its role is not elucidated yet. In this work, using different rat retina in vitro models (whole retina, retinal cells in culture, microglial cell cultures, rat Müller cell line and retina endothelial cell line), we demonstrated that NPY staining is present in the retina in different cell types: neurons, macroglial, microglial and endothelial cells. Retinal cells in culture express NPY Y1, Y2, Y4 and Y5 receptors. Retina endothelial cells express all NPY receptors except NPY Y5 receptor. Moreover, NPY is released from retinal cells in culture upon depolarization. In this study we showed for the first time that NPY is present in rat retina microglial cells and also in rat Müller cells. These in vitro models may open new perspectives to study the physiology and the potential pathophysiological role of NPY in the retina.